Visual Field Advantage: Redefined by Training? - Stone, Scott A.; Baker, Jared; Olsen, Rob; Gibb, Robbin; Doan, Jon; Hoetmer, Joshua; Gonzalez, Claudia L. R. (Frontiers in Psychology, 2019)
In 1990, Fred Previc postulated that most peri-personal space interactions occurred in the lower visual field (LVF), leading to an advantage when compared to the upper visual field (UVF). It is not clear if extensive practice can affect the difference between interactions in the LVF/UVF. We tested male and female basketball varsity athletes and non-athletes on a DynaVision D2 visuomotor reaction task. We recruited basketball players because in their training they spend significant amount of time processing upper visual field information. We found a lower visual field advantage in all participants, but this advantage was significantly reduced in the athletes. The results suggest that training can be a powerful modulator of visuomotor function.